The Semiotics of Development: Towards the Economics of Path Dependence - Macedo, Luís (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2020)
Development is a concept whose ontological foundations are include phenomena, such as technologies, institutions, and cultural traits that embody the determinants of development differentials. This contribution argues that semiotics is the science to study these complex phenomena of development. Its approach is based on Charles Sanders Peirce’s semiotics and John Searle’s analysis of social reality. Development trajectories are depicted as specific compounds of institutions (signs), technologies (objects), and markets (interpretants) that create meaningful properties depending on symbolic forms. Development is a socially structured and observer-relative phenomenon. Developmental semiosis depends upon symbolic powers that structure and assemble collective intentionality. The paper advances two critical conditions essential to development. The first is semiotic intra-coherence, which is related with the bridging of dispositional functions in a coordinated way in networks of artifacts and users. The second is inter-coherence. It takes place as the supervenient causality of social structures and the performative character of habitual patterns of behavior. Both are intertwined in syntactic and semantic forms evolving in time by forging the development of path-dependent trajectories.